A Modularly Designed Supramolecular Organocatalyst as an Effective Stimulant for the Highly Asymmetric Michael Addition of Ketones to Nitro Olefins. Issue 29 (9th September 2015) - Ramachary, Dhevalapally B.; Shruthi, Kodambahalli S.; Madhavachary, R.
Abstract: The asymmetric modularly designed supramolecular organocatalytic nitro olefin–ketone Michael addition of a variety of functionally rich nitro olefins with ketones was explored. The modularly designed supramolecular organocatalytic Michael reaction is characterized by a high rate, high chemoselectivity, high diastereoselectivity, high enantioselectivity, mild reaction conditions, readily available substrates/catalysts with simple operations, and excellent yields with a broad spectrum of functionally rich substrates. This method constitutes an alternative to previously known organocatalytic Michael reactions. Abstract : We demonstrate the power of a supramolecular organocatalyst as an excellent stimulant for the highly reactive Michael addition of various ketones with functionally rich ( E )‐nitro olefins under ambient conditions to furnish enantiomerically pure carbamates and tetrahydroacridines; Cbz = benzyloxycarbonyl.